The Effect of Storage Duration on Total Microbes of Robusta Magelang Coffee Stored in Different Types of Packaging and Temperatures - Wulan, Rahayu; Putri, Soraya Kusuma; Gunawan, Muhammad Iqbal Fanani; Sitepu, Sandy Haganta; Anggistya, Kintan Sekar (Jurusan Ilmu dan Teknologi Pangan Universitas Halu Oleo, 2025)
Indonesians prefer Robusta coffee due to its bitter taste derived from caffeine and phenolic compounds. In Central Java, Magelang and Temanggung are Arabica and Robusta coffee production centers. Packaging is an essential factor in maintaining quality and preventing the entry of microbiological contamination in coffee grounds. This study aimed to analyze the effect of storage time on the microbial characteristics of Magelang Robusta coffee grounds stored in kraft paper and aluminum foil packaging at room temperature (25 °C) and -4 °C. Microbiological analysis was carried out by calculating the Total Plate Count (TPL) based on SNI 8964:2021 for ground coffee, and was observed on the 0, 15, 30, and 45 days of storage. The results showed that at the beginning of storage, the ground coffee had a water content of 4.04%, pH 5.67, caffeine 9.38 mg/g, and total phenolics 53.74 mg GAE/g. The initial ALT value of Magelang Robusta ground coffee (5.6×104 colonies/g) was still below the SNI quality standard (106 colonies/g). The longer the storage time, the total microbes of ground coffee in both packages decreased from 4.66 to 2.72 - 3.10 log CFU/g. The high total phenolic content in ground coffee stored airtight can kill microbes in coffee. This study concluded that ground coffee with kraft paper and aluminum foil packaging at different temperatures did not significantly affect the total microbes. Still, the total microbes decreased with increased storage time.